One for the Murphys - Hunt, Lynda Mullaly (Puffin Books, 2013)
After being placed with the Murphys, a foster family, twelve-year-old Carley feels out of place and decides to keep her distance. Gradually, however, she learns to look at the Murphys as a real family, and even considers a future with them -- until sudden news from her mother throws her entire world into question.